Quantifying propagation characteristics of unconfined turbidity currents interacting with an obstacle within the slumping regime. Issue 4 (4th July 2019) - Wilson, Richard I; Friedrich, Heide; Stevens, Craig
ABSTRACT: Experimental studies of confined turbidity currents interacting with obstacles have become popular over the last three decades; however, little work has sought to quantify the characteristics of unconfined turbidity currents interacting with obstacles. In the present study, unconfined turbidity currents colliding with a rectangular basal obstruction are investigated. With a focus on the initial theoretical slumping regime, flow characteristics are quantified and characterized. The currents varied with initial density and substrate roughness. Unobstructed currents propagated at a constant velocity, confirming previous theory that the current is within the slumping regime; however, a typical reverse ambient bore was not present. Froude and Reynolds numbers were shown to decrease over the obstacle by 43–54% and 17%, respectively. Deflected lateral propagation along the obstacle face was found to entrap ambient fluid and encourage mixing, providing a starting point for understanding the implications of lateral propagation along submerged pipelines and reservoir barriers.